LncRNA KASRT Serves as a Potential Treatment Target by Regulating SRSF1-Related KLF6 Alternative Splicing and the P21/CCND1 Pathway in Osteosarcoma: An In Vitro and In Vivo Study - Chen, Kai; Li, Cheng; Huang, Shuai; Chen, Yu; Zhu, Xiaodong (Frontiers in Oncology, 2021)
Purpose: Long non-coding RNA KLF6 alternative splicing regulating transcript (lnc-KASRT) locates within the intronic region of SRSF1, possess the potential to regulate KLF6 alternative splicing to promote carcinogenicity. Then the current in vitro and in vivo study aimed to investigate the effect of lnc-KASRT on regulating tumor malignant behaviors, and the implication of its interaction with KLF6 alternative splicing in osteosarcoma. Methods: Lnc-KASRT overexpression or knockdown plasmid was transfected into U-2OS and Saos-2 cells. Then KLF6-SV1 knockdown plasmid with or without lnc-KASRT overexpression plasmid were transfected into these cells for compensative experiments. In vivo, lnc-KASRT overexpression or knockdown Saos-2 cells were injected in mice for tumor xenografts construction. Results: Lnc-KASRT expression was increased in most osteosarcoma cell lines compared to control cell line. Lnc-KASRT overexpression promoted cell viability, mobility, anti-apoptotic marker expression, while reduced apoptosis rate and pro-apoptotic marker expression; meanwhile, it regulated SRSF1, KLF6 alternative splicing (increased KLF6-splice variant 1 (KLF6-SV1), decreased KLF6-wild type (KLF6-WT)), and followed P21/CCND1 pathway in U-2OS/Saos-2 cells. The lnc-KASRT knockdown exhibited opposite trends. Subsequent compensative experiments disclosed that KLF6-SV1 knockdown attenuated most of the tumor-promoting effects of lnc-KASRT overexpression in U-2OS/Saos-2 cells. In vivo experiments further validated that lnc-KASRT enhanced tumor growth, reduced tumor apoptosis; meanwhile, it also increased tumor KLF6-SV1, MMP-1 and MMP-9 expressions while decreased tumor SRSF1 and KLF6-WT expressions in xenograft mice. Conclusion: Lnc-KASRT serves as a potential treatment target via regulating SRSF1-related KLF6 alternative splicing and followed P21/CCND1 pathway in osteosarcoma.